Metallic Materials for Hydrogen Storage—A Brief Overview - Hájková, Pavlína; Horník, Jakub; Čižmárová, Elena; Kalianko, František (Coatings (Basel), 2022)
The research and development of materials suitable for hydrogen storage has received a great deal of attention worldwide. Due to the safety risks involved in the conventional storage of hydrogen in its gaseous or liquid phase in containers and tanks, development has focused on solid-phase hydrogen storage, including metals. Light metal alloys and high-entropy alloys, which have a high potential for hydrogen absorption/desorption at near-standard ambient conditions, are receiving interest. For the development of these alloys, due to the complexity of their compositions, a computational approach using CALPHAD (Calculation of Phases Diagrams) and machine learning (ML) methods that exploit thermodynamic databases of already-known and experimentally verified systems are being increasingly applied. In order to increase the absorption capacity or to decrease the desorption temperature and to stabilize the phase composition, specific material preparation methods (HEBM—high-energy milling, HPT—high-pressure torsion) referred to as activation must be applied for some alloys.